Liquidity preference theory revisited: to ditch or to build on it? - Jörg Bibow (Levy Economics Institute of Bard College, 2005)
This paper revisits Keynes's liquidity preference theory as it evolved from the Treatise on Money to The General Theory and after, with a view of assessing the theory's ongoing relevance and applicability to issues of both monetary theory and policy. Contrary to the neoclassical special case interpretation, Keynes considered his liquidity preference theory of interest as a replacement for flawed saving or loanable funds theories of interest emphasizing the real forces of productivity and thrift. His point was that it is money, not saving, which is the necessary prerequisite for economic activity in monetary production economies. Accordingly, turning neoclassical wisdom on its head, it is the terms of finance as determined within the financial system that rule the roost to which the real economy must adapt itself. The key practical matter is how deliberate monetary control can be applied to attain acceptable real performance. In this regard, it is argued that Keynes's analysis offers insights into practical issues, such as policy credibility and expectations management, that reach well beyond both heterodox endogenous money approaches and modern Wicksellian orthodoxy, which remains trapped in the illusion of money neutrality.
Keywords: B22; B31; B41; E12; E43; E52; 330; liquidity preference theory; interest rate determination; loanable funds fallacy; bank behavior; monetary policy; credibility; liquidity traps; money neutrality